BRAZILIAN MEDICAL DEMOGRAPHY COMPARED TO THE USA AND THE EUROPEAN UNION: A BIBLIOGRAPHICAL REVIEW - Silva Mariano, Liz; Meireles Franklin, Matheus Lucas; Augusto Colla, Mauricio; Rodrigues Borges, Maria Eduarda; Moita Sant'Anna, Guilherme; de Lima Filho, Antonio Vidal; Bonfá Camillo, Bruno Rheuly; Durães de Araújo, Jade Luiza; Silva de Melo, Brenno; Vieira Santos, Daniel; Souza de Vasconcelos, Rhuan Pablo; Vasconcelos Perboni, Marianna (Brazilian Journal of Implantology and Health Sciences, 2024)
The study addresses medical demographics in Brazil, comparing them with the scenarios in the United States (US) and Europe, analyzing the distribution, density, and training of doctors. In Brazil, the number of doctors more than doubled between 2000 and 2023, rising from 219,000 to 562,000 professionals, with a current density of 2.6 doctors per 1,000 inhabitants. This growth is the result of the expansion of places in medical courses, mainly in private institutions, driven by the More Doctors Law of 2013. However, challenges persist, such as the concentration of general practitioners due to the bottleneck of vacancies in residencies and issues related to the quality of training for these professionals. The methodology was based on the analysis of data available in the book Medical Demography in Brazil of 2023 and in articles available on the PubMed platform. In the US, a shortage of 139,160 doctors is expected by 2030; even with the increase in the number of graduates, there is still a limitation of vacancies in residency programs. The current density is 2.64 doctors per 1,000 inhabitants, similar to that of Brazil. In Europe, the average density in 2017 was 3.5 doctors per 1,000 inhabitants, above the Brazilian and American averages. Brazil is on track to reach a medical density similar to that of developed countries by 2030, with projections of 4 doctors per 1,000 inhabitants. However, challenges persist, such as poor regional distribution, low quality training and a shortage of specialists. Public policies need to align the expansion of the workforce with improved training and equitable distribution, ensuring greater efficiency and more places for specialization.